Social networking friendships: A cross-cultural comparison of network structure between MySpace and Wretch - Chang Hui-Jung (Cultural Science)
A cross-cultural comparison of social networking friendship between MySpace (in USA) and Wretch (in Taiwan) was conducted utilizing the high- and low-context framework proposed by Edward T. Hall (1976). Three network indicators were used to describe the network structure of both social network sites: size, density, and heterogeneity. Data were drawn from the forum “Jobs, Work, Careers” on MySpace and “Job-Related” on Wretch over a 2-month period from mid-October to mid-December in 2007. For each of the 2 sites, 6 users (3 men and 3 women) were randomly selected as sources or “seeds” from which to crawl the friendship networks. From the 6 seed users, a snowball sample was constructed by crawling 2 degrees out along the networks. The results indicated that Wretch, although it followed the expected direction predicted by Hall’s model, did not have significantly larger and denser networks than MySpace. Finally, no differences in same-sex and cross-sex friendships were found between the 2 sites either. The overall findings are discussed with implications for future studies.